Pulsar timing arrays and primordial black holes from a supercooled phase transition - Alberto Salvio (Physics Letters B, 2024)
An explicit realistic model featuring a supercooled phase transition, which allows us to explain the background of gravitational waves recently detected by pulsar timing arrays, is constructed. In this model the phase transition corresponds to radiative symmetry breaking (and mass generation) in a dark sector featuring a dark photon associated with the broken symmetry. The completion of the transition is ensured by a non-minimal coupling between gravity and the order parameter and fast reheating occurs thanks to a preheating phase. Finally, it is also shown that the model leads to primordial black hole production.